2022
DOI: 10.3389/fmicb.2022.963488
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and COVID-19: Long-term and complex influencing factors

Abstract: The coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). According to the World Health Organization statistics, more than 500 million individuals have been infected and more than 6 million deaths have resulted worldwide. Although COVID-19 mainly affects the respiratory system, considerable evidence shows that the digestive, cardiovascular, nervous, and reproductive systems can all be involved. Angiotensin-converting enzyme 2 (AEC2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 220 publications
0
27
0
Order By: Relevance
“…The use of polyphenols, probiotics, vitamin D and omega-3 fatty acids was suggested by Daoust et al [ 204 ]. Fecal transplant, microbiota transplantation, probiotics, prebiotics, microbiome-derived metabolites, and engineered symbiotic bacteria as treatment options that could modulate host microbiota and mitigate virus-induced inflammation in the gut have been suggested by different studies [ 205 , 206 , 207 , 208 ].…”
Section: Treatment: Targeting Latent Viral Reactivation and Microbiot...mentioning
confidence: 99%
“…The use of polyphenols, probiotics, vitamin D and omega-3 fatty acids was suggested by Daoust et al [ 204 ]. Fecal transplant, microbiota transplantation, probiotics, prebiotics, microbiome-derived metabolites, and engineered symbiotic bacteria as treatment options that could modulate host microbiota and mitigate virus-induced inflammation in the gut have been suggested by different studies [ 205 , 206 , 207 , 208 ].…”
Section: Treatment: Targeting Latent Viral Reactivation and Microbiot...mentioning
confidence: 99%
“…When pathogens are eradicated with antibiotic therapy, the typical commensal microbiota may be indiscriminately eliminated, resulting in dysbiosis of the microecosystem. Compared to healthy controls, antibiotic therapy in COVID-19 patients can significantly affect intestinal flora [ 48 ]. Antibiotic overuse may have increased during the COVID-19 pandemic due to people buying antibiotics online pharmacies rather than visiting doctors in hospitals, as previously mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…ABO blood groups and Secretor/FUT2 status have already been associated with gut microbiome characteristics [21]. Several studies have shown that SARS-CoV-2 infection has negative effects on the respiratory, intestinal and oral microbiota [55],…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%